(untitled) (diségno, 2022)
Drawing, a synthetic dialogical expression that does not require words, has been profoundly transformed by the digital transition, and the same happened for design. The semantic distinction between drawing and design (understood one as a fundamental tool of representation and communication of the project, and the other as an action of sense projected onto reality through artifacts) has established itself with the emergence of new technologies and tools. Culturally this distinction, as can also be seen from the writings of the Italian masters, indicates only different phases of the project, in which the act of drawing is ‘concrete thought’, the moment in which the possible appears. [read more]